A Review of Nature and Relevance of Cricket: - (Journal of Advances and Scholarly Researches in Allied Education, 2023)
One of the oldest sports being played today, cricket has widespread recognition. Cricket'sdecline was probably traced back to the eighteenth century. In the past, it had become a trademark ofEnglish royals. With the help of gambling cricket, aristocrats such as kings and dukes left their palacesearly. The aim of the study is to understand the nature and relevance of Cricket. In this we focus on thesports physiology and cricket performance, nature of cricket and Relevance of cricket in details.